2013
DOI: 10.1103/physrevd.88.052017
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of searches for supersymmetry with simplified models

Abstract: The results of searches for supersymmetry by the CMS experiment are interpreted in the framework of simplified models. The results are based on data corresponding to an integrated luminosity of 4.73 to 4.98  fb−1. The data were collected at the LHC in proton–proton collisions at a center-of-mass energy of 7 TeV. This paper describes the method of interpretation and provides upper limits on the product of the production cross section and branching fraction as a function of new particle masses for a number of si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
123
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 49 publications
0
123
0
Order By: Relevance
“…The LHC has started to test the electroweak (EW) sector of the MSSM in a class of searches involving different multiplicities of leptons, no jets, and a significant amount JHEP06(2015)020 of missing energy. The 8 TeV run has provided strong lower bounds on chargino and slepton masses, in particular when interpreted in the framework of simplified model spectra (SMS) [34]. However, several studies have shown [19,22,23,28,29] that if the experimental limits provided by the CMS and ATLAS collaborations are reinterpreted and applied to more general MSSM scenarios the 8 TeV LHC results can only constrain a small part of the available parameter space, so that ample room still remains to attribute a supersymmetric (SUSY) origin to δ (g − 2) µ .…”
Section: Introductionmentioning
confidence: 99%
“…The LHC has started to test the electroweak (EW) sector of the MSSM in a class of searches involving different multiplicities of leptons, no jets, and a significant amount JHEP06(2015)020 of missing energy. The 8 TeV run has provided strong lower bounds on chargino and slepton masses, in particular when interpreted in the framework of simplified model spectra (SMS) [34]. However, several studies have shown [19,22,23,28,29] that if the experimental limits provided by the CMS and ATLAS collaborations are reinterpreted and applied to more general MSSM scenarios the 8 TeV LHC results can only constrain a small part of the available parameter space, so that ample room still remains to attribute a supersymmetric (SUSY) origin to δ (g − 2) µ .…”
Section: Introductionmentioning
confidence: 99%
“…7 and Ch. 8 for gluino pair production based on three-body gluino decays, in which each gluino decays to one of the following final states [95]: The simplified natural SUSY spectrum considered in this thesis, along with the assumed decay modes [94,44].…”
Section: Simplified Natural Supersymmetry Modelsmentioning
confidence: 99%
“…However, these limits are usually derived under the assumption that the SUSY particle mass spectrum resembles one of a set of simplified models [19][20][21]. Because this set does not cover the entire range of experimentally possible outcomes allowed by the minimal supersymmetric standard model (MSSM), it is informative to perform a global interpretation of searches in terms of a model that better covers the MSSM to assess the viability of the weak-scale SUSY hypothesis.…”
Section: Introductionmentioning
confidence: 99%